Efforts to Increase Elementary Students' Interest in Learning through the Implementation of Role Playing Strategies in Learning Indonesian at SD/MI - Wahyu Azhari (Yayasan Zia Salsabila, 2023)
Boredom in the learning process is not something that is rarely encountered in class. It is hoped that with the right learning strategy it can attract students' attention and increase students' enthusiasm and interest in learning, therefore the right strategy is needed so that students are not bored and bored when learning is in progress. This paper aims that learning strategies, especially learning strategies for Role Playing can minimize student boredom and create an exciting classroom atmosphere. The type of this research is qualitative using data collection techniques in the form of observation and documentation. From this study it can be found that: (1) students participate actively and focus on playing a role, (2) students seem happy when playing a character/role in the fictional story.